A Nogo-Like Signaling Perspective from Birth to Adulthood and in Old Age: Brain Expression Patterns of Ligands, Receptors and Modulators - Smedfors, Gabriella; Olson, Lars; Karlsson, Tobias E. (Frontiers in Molecular Neuroscience, 2018)
An appropriate strength of Nogo-like signaling is important to maintain synaptic homeostasis in the CNS. Disturbances have been associated with schizophrenia, MS and other diseases. Blocking Nogo-like signaling may improve recovery after spinal cord injury, stroke and traumatic brain injury. To understand the interacting roles of an increasing number of ligands, receptors and modulators engaged in Nogo-like signaling, the transcriptional activity of these genes in the same brain areas from birth to old age in the normal brain is needed. Thus we have quantitatively mapped the innate expression of 11 important genes engaged in Nogo-like signaling. Using in situ hybridization, we located and measured the amount of mRNA encoding Nogo-A, OMgp, NgR1, NgR2, NgR3, Lingo-1, Troy, Olfactomedin, LgI1, ADAM22 and MAG, in 18 different brain areas at six different ages (P0, 1 w, 2 w, 4 w, 14 w and 104 w). We show gene- and area-specific activities and how the genes undergo dynamic regulation during postnatal development and become stable during adulthood. Hippocampal areas underwent the largest changes over time. We only found differences between individual cortical areas in Troy and MAG. Subcortical areas presented the largest inter-regional differences; lateral and basolateral amygdala had markedly higher expression than other subcortical areas. The widespread differences and unique expression patterns of the different genes involved in Nogo-like signaling suggest that the functional complexes could look vastly different in different areas.